دراسة مخبريّة مقارنة لتأثير التحضير بكتف والتحضير بشبه كتف على الإنطباق الحفافي في التيجان الزركونية الخزفيّة المصنعة بتقنية CAD-CAM وتأثير دورات خبز الخزف على هذا الإنطباق - بهرلي ناصر; بدور جهاد; شموط محمد (Latakia University Journal -Medical Sciences Series, 2016)
بما أنّ الإنطباق الحفافي هو العامل الأساسي في إطالة عمر والنجاح السريري للتعويض السني الثابت، فقد هدف هذا البحث لقياس التغيرات في الإنطباق الحفافي للقلنسوات الزركونية المصنعة بتقنية التصميم و التصنيع باستخدام الحاسب CAD-CAM قبل و بعد دورات خبز الخزف باستخدام تصميمين مختلفين من خطوط الإنهاء، وذلك لتعزيز عوامل نجاح التيجان الزركونية الخزفية. تمت دراسة هذا التغير في الإنطباق الحفافي باستخدام نموذجين قياسيين من الستانلس ستيل لثنية علوية محضرة لاستقبال تاج زيركوني خزفي بخط إنهاء على شكل كتف وآخر على شكل شبه كتف. جرى تصنيع 20 قلنسوة زيركونية باستخدام تقنية التصميم والتصنيع بمساعدة الحاسبCAD/CAM ، بقياس افتراضي للفجوة الحفافية صفر ميكرون. قسمت إلى 10 قلنسوات بكتف و 10 قلنسوات بشبه كتف . و أجريت القياسات باستخدام مجهر ضوئي مزود بكاميرا( WM2BV®-Germany ) بتكبير 500 مرة. لوحظ بأن دورات خبز الخزف أحدثت زيادة في الفجوة الحفافية ما بين حافة التاج الزيركوني الخزفي وحافة السن المحضر وأظهرت النهاية العنقية بشكل كتف تغيراً حفافياً أقل من شبه الكتف عندما تمت المقارنة من حيث شكل خط الإنهاء عند تطبيق اختبار t student و اختبار Mann Whitney و تحليل التباين الأحاديunivariate analysis of variance ) ANOVA (. كما لوحظ أيضا أن قيم الانطباق الحفافي في الدراسة الحالية كانت ضمن الحدود المقبولة سريريا . The marginal fit is the essential factor of prolonging age and clinical success of fixed prosthodontics . The aim of this study was to measure changes of the marginal fit of the zirconia copings fabricated using CAD-CAM system before and after the ceramic firing cycles by using two different finishing line designs, and that to promote success factors of the zirconia-ceramic crowns. The study of this change in the marginal fit is achieved by using two standardized models made of stainless steel , one with a shoulder margin and the other with a chamfer margin , which represented preparations for zirconia - ceramic restorations of a maxillary central incisor. Twenty zirconia copings were fabricated using a CAD/CAM system with hypothetical size of marginal gap 0 micron, and divided into ten with a shoulder and other ten with a chamfer. Measurements were carried out by using a microscope with camera ( WM2BV®-Germany ) at 500-times magnification. It was noticed that comparisons of the firing cycles revealed a great change in the marginal gap. The cervical end with a shoulder revealed a marginal fit change less than that with a chamfer when the comparison is accrued depending on the marginal design depending on t student , Mann Whitney , univariate analysis of variance (ANOVA) tests. It was also observed that the marginal fit values in the present study were all within the clinically acceptable range.